Examining the effects among motivation needs, satisfaction, and Instagram continuance intention in Malaysian students - Jin, Dian; Abas, Wan Anita Wan; Kamarudin, Syafila (Redfame Publishing Inc., 2024)
While social media platforms, notably Instagram, have gained traction among university students, this study sought to understand factors influencing their continued use among a segment of Malaysian university students. The primary purpose of this study was to examine the role of satisfaction (SAT) as a mediator in the relationship between various types of motivational needs and the continued intention (CI) to use Instagram. The motivational needs under study included cognitive needs (CN), affective needs (AN), personal integrative needs (PIN), social integrative needs (SIN), and escape needs (EN). This research was built on the foundations of the Uses and Gratifications Theory (UGT) and Expectation Confirmation Theory (ECT). Using a non-probablistic sampling strategy, this study gathered data via questionnaires from a sample of 384 students from six selected universities in Klang Valley. Within the scope of the research sample, a key finding emerged: SAT notably mediates the relationship between CN, SIN, PIN, and CI. This finding illustrates the pivotal role of SAT in the context of UGT and ECT, suggesting that SAT derived from Instagram usage is a critical factor in explaining the sustained engagement of university students, based on specific motivational needs. Within the context of this study’s sampled participants, this result offers insights into how SAT, influenced by distinct motivational needs, may impact the intention to continue using Instagram. In practical terms, these insights may assist social media platform developers and educational institutions in understanding and addressing the satisfaction and engagement levels of university users. Simultaneously, the quota sampling strategy employed in this study serves as a valuable model for future research in similar contexts. However, this study recommend that future research expand the sample to include a broader cross-section of Malaysian university students to enhance representativeness and generalizability.